An extradural cyst in a French Bulldog. Issue 3 (4th May 2023) - Philips, R; Chase, D; Thompson, D; Hardcastle, M; Kiupel, M
ABSTRACT: Case history: A 7-year-old, male neutered French Bulldog was referred to a specialist veterinary hospital for evaluation of progressive paraparesis of 6-months' duration. The owners reported both faecal and urinary incontinence at home. Clinical findings: The dog presented with ambulatory paraparesis and pelvic limb ataxia that was more pronounced in the right pelvic limb. The pelvic limb withdrawal response and sciatic myotatic response were reduced bilaterally. Postural reaction responses were delayed in both pelvic limbs, and this was more obvious in the right pelvic limb. The anal tone and perineal sensation were normal at the time of examination. An L4–S3 myelopathy was suspected. CT of the spine revealed a compressive, bilobed, extramedullary, cyst-like structure within the vertebral canal, between L7 and S3. Surgical removal of the cyst via a L7–S1 dorsal laminectomy was performed. Histopathological examination and additional immunohistochemistry of the excised structure indicated a probable ependymal cyst with a ciliated lining. The dog recovered well post-operatively, and at follow-up 3 weeks later had some improvement of his neurological signs. The paraparesis and pelvic limb ataxia had improved; however, the remaining neurological examination was similar to the pre-surgical examination. Diagnosis: Extradural cyst. Clinical relevance: Spinal cysts can contribute to clinical signs that resemble other common chronic spinal cord diseases, such as intervertebral disc disease. Therefore, this disease should be considered as a differential when dealing with cases of progressive paraparesis and pelvic limb ataxia. This case report may potentially provide opportunities in the future for further understanding of the pathogenesis, behaviour, outcomes and subclassification of spinal cysts in dogs.